The book of Dash : build dashboards with Python and Plotly - Schroeder, Adam (Data analyst); Mayer, Christian (Computer scientist); Ward, Ann Marie (No Starch Press, 2022)
A swift and practical introduction to building interactive data visualization apps in Python, known as dashboards. You've seen dashboards before; think election result visualizations you can update in real time, or population maps you can filter by demographic. With the Python Dash library you'll create analytic dashboards that present data in effective, usable, elegant ways in just a few lines of code. The book is fast-paced and caters to those entirely new to dashboards. It will talk you through the necessary software, then get straight into building the dashboards themselves. You'll learn the basic format of a Dash app by building a twitter analysis dashboard that maps the number of likes certain accounts gained over time. You'll build up skills through three more sophisticated projects. The first is a global analysis app that compares country data in three areas: the percentage of a population using the internet, percentage of parliament seats held by women, and CO2 emissions. You'll then build an investment portfolio dashboard, and an app that allows you to visualize and explore machine learning algorithms.